Television viewing, physical activity and venous thromboembolism risk: The Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study. (30th June 2021) - Munger, Jordan A.; Koh, Insu; Howard, George; Howard, Virginia; Plante, Timothy B.; Wilkinson, Katherine; Cushman, Mary; Zakai, Neil A.
Abstract: Introduction: Television (TV) viewing may be associated with increased venous thromboembolism (VTE) risk independent of VTE risk factors including physical activity. This association was assessed in a large biracial US cohort of Black and White adults. Methods: Between 2003 and 2007 The Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study recruited 30, 239 participants aged ≥45 years, who were surveyed for baseline TV viewing and followed for VTE events. TV viewing was categorized as <2 hours (light), 2 to 4 hours (moderate), and ≥4 hours (heavy) per day. Physical activity was classified as poor, intermediate, or ideal based on reported weekly activity. Hazard ratios of TV viewing and physical activity were calculated adjusting for VTE risk factors. Multiple imputation for missingness was used as a sensitivity analysis. Results: Over 96, 813 person‐years (median: 5.06 years) of follow‐up there were 214 VTE events. Heavy TV viewing was not associated with VTE risk in the unadjusted and fully adjusted model (adjusted hazard ratio [aHR]: 0.92 [95% confidence interval (CI): 0.62, 1.36]). Ideal physical activity trended toward a reduced VTE risk (HR: 0.71 [95%CI: 0.51, 1.01]). There was no evidence of an interaction between TV viewing, physical activity, and risk of VTE. Conclusions: In this contemporary racially and geographically diverse US cohort, there was no association between TV viewing and VTE risk, before and after accounting for physical activity. The high burden of traditional VTE risk factors in REGARDS may mask any association of TV viewing with VTE, or TV viewing may have only a modest association with VTE risk.